Sistem Pemantauan Tekanan Air Berbasis IoT Dengan Integrasi Penyimpanan Data Online - Nur Istianto, Yudha; Muhtarom, Moh.; Purwanto, Eko (Fakultas Teknik Universitas Hamzanwadi, 2025)
Unstable water pressure in the household environment can disrupt daily activities such as bathing, washing, and cooking, and also affect comfort and the availability of clean water. To addres this issue, a system capable of monitoring water pressure in real-time is needed. This research, conducted at PAMSIMAS Dukuh Tawang, aims to design and develop an IoT-based water pressure monitoring system that can present water pressure data online. The system displays real-time water pressure graphs and provides a power ON/OFF feature accessible via an IoT platform. The development process follows the Prototyping method, which includes stages form needs identification to system evaluation. The research results are expected to show that the system performs well in monitoring water pressure in real-time with good accuracy and provides users with informative graphical displays. The implementation of this system is considered at affective in supporting the management of clean water distribution at the household level and contributes to helping the community anticipate water distribution disruptions and improve the quality of access to a more stable and monitored water supply.